2018
DOI: 10.1038/s41563-018-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic luminal coating of the intestine

Abstract: The gastrointestinal tract is the site of most drug delivery and therapeutic interventions for the management and treatment of numerous diseases. However, selective access to its mucosa, especially in the small bowel, is challenging. Here we develop an orally administered gut-coating formulation that provides a transient coating of the bowel. Through a materials screening campaign, we identified a sucrose octasulfate aluminium complex and further engineered the pH-dependent material into a complex coacervate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…CT imaging and IVIS were used to visualize the biomimetic intestinal barrier on the gut surface in vivo [14]. In CT imaging, sucralfate was composed with diodone and encapsulated in microcapsules for gavage.…”
Section: Characterization Of the Intestine Physical Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…CT imaging and IVIS were used to visualize the biomimetic intestinal barrier on the gut surface in vivo [14]. In CT imaging, sucralfate was composed with diodone and encapsulated in microcapsules for gavage.…”
Section: Characterization Of the Intestine Physical Barriermentioning
confidence: 99%
“…1. Benefiting from their capability to separate liquid cargo and solid encapsulant as well as high cargo content, microcapsules have been widely applied in encapsulation, delivery, and release of actives in the fields of agriculture, cosmetics, drug delivery, detergents, and food additives [14][15][16][17][18]. A variety of techniques, such as spray drying, interfacial polymerization, complex coacervation, and microfluidics, have been employed for the preparation of functional microcapsules [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, group C (fed with high-fat food & H-field) and group D (fed with high-fat food & E-capsules) presented a relatively low absorption of xylose. This result was due to the presence of hydrophilic methylcellulose, the main component of the capsule, which could adsorb small water-soluble molecules and reduce absorption through the small intestine 29 . This result also indicated that the method could effectively decrease the absorption of water-soluble substances but would not form an effective barrier for fat-soluble substances.…”
Section: Tc Tg and D-xylose Absorptionmentioning
confidence: 99%
“…Another essential function of the small intestine is regulation of plasma glucose concentrations, which are frequently associated with metabolic disorders and systemic diseases, such as obesity, hyperinsulinemia, and diabetes mellitus (36). To modulate nutrient absorption in patients with these disorders, treatments such as gastric bypass surgery, intestinal sleeve placement, intestinal mucosal resurfacing, surgical adhesives, and GI electrical stimulation have been applied (5,6,8,37,38). However, these procedures can be invasive and manifest with adverse effects.…”
Section: Introductionmentioning
confidence: 99%